Host Response to Biomaterials for Cartilage Tissue Engineering: Key to Remodeling - Wei, Fu; Liu, Shuyun; Chen, Mingxue; Tian, Guangzhao; Zha, Kangkang; Yang, Zhen; Jiang, Shuangpeng; Li, Muzhe; Sui, Xiang; Chen, Zhiwei; Guo, Quanyi (Frontiers in Bioengineering and Biotechnology, 2021)
Biomaterials play a core role in cartilage repair and regeneration. The success or failure of an implanted biomaterial is largely dependent on host response following implantation. Host response has been considered to be influenced by numerous factors, such as immune components of materials, cytokines and inflammatory agents induced by implants. Both synthetic and native materials involve immune components, which are also termed as immunogenicity. Generally，the innate and adaptive immune system will be activated and various cytokines and inflammatory agents will be consequently released after biomaterials implantation, and further triggers host response to biomaterials. This will guide the constructive remolding process of damaged tissue. Therefore, biomaterial immunogenicity should be given more attention. Further understanding the specific biological mechanisms of host response to biomaterials and the effects of the host-biomaterial interaction may be beneficial to promote cartilage repair and regeneration. In this review, we summarized the characteristics of the host response to implants and the immunomodulatory properties of varied biomaterial. We hope this review will provide scientists with inspiration in cartilage regeneration by controlling immune components of biomaterials and modulating the immune system.